Pengaruh Perceived Organizational Support terhadap Employee Engagement pada Dosen - Gayatri Mazaya Khairana Umbara; Dinda Dwarawati (Bandung Conference Series: Psychology Science, 2024)
Abstract. Employee Engagement" refers to the cognitive, emotional, and behavioral condition of employees directed towards desired company outcomes (Shuck and Wollard, 2010). "Perceived Organizational Support," as defined by Eisenberger et al. (1986), is the perception of how much employees feel the organization values their contributions while caring for their well-being during employment. This study aims to determine the influence of Perceived Organizational Support on Employee Engagement among lecturers. The research method employed in this study is quantitative. The subjects of this study are lecturers at private universities in the city of Bandung with an "Excellent" accreditation, totaling 116 individuals. The data analysis technique used is multiple linear regression. The measurement tools used in this research include the Perceived Organizational Support instrument developed by Eisenberger, Huntington, Hutchinson, & Sowa (1986) and adapted by Meilian, Idulfilastri, and Dewi (2020) with 36 items, and the Employee Engagement Scale (EES) developed by Shuck et al. (2016) and adapted by Astari, Kadiyono, and Batubara (2022) with 12 items. The results of this study indicate that Perceived Organizational Support has an influence of 42.7% on Employee Engagement. Supervisor Support has the most significant influence on Employee Engagement, accounting for 26.1%. Meanwhile, Fairness does not have a significant impact on Employee Engagement. Abstrak. Employee Engagement merupakan kondisi kognitif, emosional, dan perilaku karyawan yang diarahkan menuju hasil perusahaan yang diinginkan (Shuck dan Wollard, 2010). Perceived Organizational Support menurut Eisenberger et al., (1986) merupakan persepsi karyawan mengenai sejauh mana organisasi menghargai kontribusi mereka selama bekerja dan peduli akan kesejahteraan mereka. Penelitian ini bertujuan untuk mengetahui pengaruh Perceived Organizational Support terhadap Employee Engagement pada dosen. Metode yang digunakan pada penelitian ini adalah metode kuantitatif. Subjek pada penelitian ini adalah dosen perguruan tinggi swasta di Kota Bandung dengan akreditasi Unggul sebanyak 116 orang. Teknik analisis data yang digunakan adalah regresi linier berganda. Alat ukur yang digunakan dalam penelitian ini adalah alat ukur Perceived Organizational Support yang dikembangkan oleh Eisenberger, Huntington, Hutchinson, & Sowa (1986) dan diadaptasi oleh Meilian, Idulfilastri, dan Dewi (2020) dengan 36 item dan alat ukur Employee Engagement Scale (EES) yang dikembangkan oleh Shuck et al (2016) yang diadaptasi oleh Astari, Kadiyono, dan Batubara (2022) dengan 12 item. Hasil penilitian ini menunjukkan bahwa Perceived Organizational Support memberikan pengaruh sebesar 42.7% terhadap Employee Engagement. Supervisor Support memberikan pengaruh paling besar pada Employee Engagement yaitu sebesar 26.1%. sedangkan, Fairness tidak berpengaruh terhadap Employee Engagement.